The impact of driving time, distance, and socioeconomic factors on outcomes of patients with locally advanced rectal cancer - Joanna Gotfrit; Tharshika Thangarasa; Shaan Dudani; Rachel Goodwin; Patricia A. Tang; Jose Monzon; Kristopher Dennis; Winson Y. Cheung; Horia Marginean; Michael Vickers (Elsevier, 2020)
Objectives: Cancer patients experience disparities due to socioeconomic status (SES) factors. We assessed the impact of SES factors on outcomes in patients with locally advanced rectal cancer (LARC) who received neoadjuvant chemoradiation (nCRT) and surgery (Sx) in 3 Canadian provinces. Study design: This study was a multi-institutional retrospective chart review. Methods: Associations among community characteristics (2016 Canadian Census data), distance and time to the cancer center (mapping software), and outcomes were evaluated using the CHORD multi-institutional database. Results: 1,064 patients were included. Median age 62, 68% male, 15% lived in a rural community, 19% with median community household income >$50,000 CAD, median community proportion with post-secondary education 66%, 12% lived >100km away, and 18% lived >1 ​h away.Factors predictive of worse disease-free survival (DFS) and overall survival (OS) in univariate analysis included driving time >1 ​h, median community income ≤$50,000 CAD, driving distance >100km, and lower median community proportion with post-secondary education. Driving time >1 ​h remained significant in multivariate analysis for worse DFS (HR 1.47; 95% CI 1.14-1.90; p ​= ​0.003) and OS (HR 1.60, 95% CI 1.19-2.16; p ​= ​0.002). Conclusion: Outcomes of patients with LARC undergoing nCRT are negatively associated with increased driving time to the cancer centre.